Anatomical Differences in the Omasum of Weaning Calves Fed with Different Diets - William Pérez; Sokol Duro; Ozan Gündemir (MDPI AG, 2023)
The omasum is the third compartment of the ruminant stomach, which is also considered a water absorption organ and participates in the absorption of volatile fatty acids (VFA), minerals, electrolytes, and fluids. The most important morphological parameter of the omasum is the available absorption area, which depends on the size and number of the omasal laminae, and is variable among different ruminants and based on differences in their daily diets. Optimal omasum development in the transition period to ruminant life can enhance animal performance, so identifying the best diet for this period is crucial for producers. The objective of this study was to determine the effect of two diets based on 8 L of milk replacer with the inclusion of concentrate or forage on the development of the omasum in twenty newborn male Holstein calves divided into two groups. The first group was fed alfalfa hay, and the second was administered a balanced commercial starter feed, both groups ad libitum. After standard dissection of the omasum of both calf groups, the omasal laminae were classified as primary, secondary, and tertiary, and their surface area was calculated. Regarding the number of first-, second-, and third-order laminae, a significant difference was only observed in the number of third-order laminae in favor of the forage-fed group (p = 0.04). The laminar surface area indicated that the area of the primary, secondary, and tertiary sheets, and the total laminar area, were greater in the forage group (p < 0.05). The length of the omasal papillae recorded with the scanning electron microscope showed that the papillae near the ostium reticulo-omasicum tended to be significantly longer in the forage-fed group (p = 0.05). In conclusion, this study demonstrates that significant anatomical differences can be observed between two groups of animals of the same species and rearing stage that were fed with two different diets within a period of less than two months. This highlights the remarkable plasticity and adaptability of the ruminant stomach.